Implementing the nature's contributions framework: A case study based on farm typologies in small-scale agroecosystems from the Mexico highlands - Rodríguez-Bustos, Laura; Galicia, Leopoldo; Benítez, Mariana; Palacios-Rojas, Natalia; Ramos, Irene (Frontiers in Sustainable Food Systems, 2023)
Introduction Integrating the heterogeneity of small-scale agriculture with the regulation, material, and non-material contributions is key to complementing the rural-support policy instruments. The objectives of the present study were to analyze the diversity of agricultural types of management in small-scale maize agroecosystems and discuss their implications for nature's contributions in the region of Valles Altos, México. Methods The methodology was conducted by constructing an agricultural management typology with multivariate statistical analysis for 112 small plots interviews. The operationalization of regulation, material, and non-material nature's contributions was based on the definition and counting of cultural elements from agronomic management for each class of contribution. Results The results indicate three different types of agricultural management defined mainly by the type of seed, the destination of harvest, and the type of tillage. This management diversity is guided by farmers' motivation to achieve food self-sufficiency or generate income from grain sales. Each management type has a unique provision of regulation, material, and no material contributions defined by the use of the native seed, use of stover, and management diversification. Discussion The integration of farm typology methods and nature's contributions framework reveals that it is critical to establish new incentives that include the biological and cultural diversity of agroecosystems and the individual motivations of farmers. This may help conserve the natural and cultural values of agriculture and design appropriate incentives for small-scale agriculture.